Notices (Blackfriars, 1940)
MARY OF NAZARETH. By Vincent McNabb, O.P. CONSTRUCTION DE LA PAIX. Paroles d'un Théologien. Par le Père Th. Derman, O.P. MEDITATIONS ON THE LOVE OF GOD. By Diego de Estella. L'IDÉE DE LA VIE RELIGIEUSE. Par Benoit Lavaud, O.P. LA MESSE ROMAINE. Par L. Caron. BLAVATSKY, BESANT. AND Co. By T. M. Francis, with a preface by Fr. Herbert Thurston, S.J. THE CHURCH BEFORF PILATE. By Edward Leen, C.S.Sp.